Audit Risk, Professional Skepticism, And Audit Quality: The Moderating Role of Utilization of Information Technology - Al Farishi, Ryandika Ramadhan; Salim, Susanto (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This research aims to analyze the effect of audit risk (AR) and professional skepticism (PS) on audit quality (AQ), with the utilization of information technology (UIT) as a moderating variable at Public Accountant Firms (PAF) in Jakarta. The novelty of this study lies in its examination of how technological integration may influence the relationship between auditor behavior and audit quality—a topic that remains underexplored in the Indonesian auditing context. This research employs a quantitative approach with 163 auditor respondents from both Big Four and non-Big Four PAFs. Data were analyzed using the SEM-PLS (Structural Equation Modeling - Partial Least Squares) method with SmartPLS 4.0. The results reveal that AR and PS significantly affect AQ, but UIT does not significantly moderate the relationship between AR or PS and AQ. These findings provide insights for PAFs to enhance audit quality by strengthening professional skepticism and managing audit risk effectively. While the moderating role of UIT was not supported, this suggests future research opportunities to explore other potential moderating variables or expand the scope to different regions or industries.